FEATURES OF MAKING DECISIONS CONDITIONED BY A THEATRE-OFWAR SITUATION WHICH DYNAMICALLY CHANGING - Victor E. Bobylov; Anatolii A. Kravchuk (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The investigation results of the process of decision-making by a commanding manager conditioned by a dynamically changing theatre-of-war situation have been revealed in the article. Hence, the main problematic issues emerging in the process of decision-making under abovementioned circumstances have been defined. While the author singled out ways and options for their solving.